Proceedings of the First ASEAN Business, Environment, and Technology Symposium (ABEATS 2019) 2020
DOI: 10.2991/aebmr.k.200514.028
|View full text |Cite
|
Sign up to set email alerts
|

The Development of New Material for Food Production Package in Indonesia: Proposed Key Success Factors

Abstract: Nowadays, it is important to reduce and replace plastic in the food manufacture industry. However, the development of new material is less than satisfactory. This paper aims to analyze the key factors for the development of new material for the food production package. A survey was conducted to gather data to test the factors in the development of new material for food production package identified by literature review, expert interviews, and distribution questionnaires to respondents. The questionnaire uses a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…This research continued the previous study to identify the critical factors which essential for the new material development and participation in food packaging (Tirdasari et al 2020). Based on the review of literature, the findings revealed that the critical success factors are classified into five clusters, namely technical substitution, technical drivers/barriers, application barriers, cost barriers, and raw material supply barriers.…”
Section: Resultssupporting
confidence: 53%
“…This research continued the previous study to identify the critical factors which essential for the new material development and participation in food packaging (Tirdasari et al 2020). Based on the review of literature, the findings revealed that the critical success factors are classified into five clusters, namely technical substitution, technical drivers/barriers, application barriers, cost barriers, and raw material supply barriers.…”
Section: Resultssupporting
confidence: 53%
“…Today, it is important to reduce and replace plastics in industry and food production. However, the development of new materials for packaging is unsatisfactory because the process is very complex (Tirdasari et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The second hypothesis concerns that there are factors that influence the decision to implement ecopackaging of vegetable products. This is based on previous research (Oktariani et al 2019) which studied one of the factors for implementing ecopackaging products, there is the availability of ecopackaging materials. This research uses the Quality Function Deployment (QFD) method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation